Linguistic and cultural variation in early color word learning - Forbes, S; Plunkett, K (John Wiley and Sons, Inc., 2018)
When and how do infants learn color words? It is generally supposed that color words are learned late, and with a great deal of difficulty. By examining infant language surveys in British English and 11 other languages, we show that color word learning occurs earlier than has been previously suggested, and that the order of acquisition of color words is similar in related languages. We demonstrate that frequency and syllabic complexity can be used to predict variability in infant color word learning across languages. In light of recent evidence indicating that color categories have universal biological foundations, these findings suggest that infants’ experience and linguistic exposure drive their shift to culturally and linguistically-mediated adult-like understandings of color words.